(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Maize (Zea mays L.) is world’s third most important cereal crop that has a remarkable productive potential in Bangladesh. In Bangladesh, maize is the second most important cereal crop in terms of production. The selection for high yield with desirable traits depends on the genetic variability in the existing germplasm. Successful breeding programs need adequate genetic variation for selection and improvement based on necessity. The research was conducted in the experimental farm of the Department of Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh during November 2015 to April 2016. The aim of this study was to evaluate the performance of 20 maize genotypes based on their yield and yield contributing characters to determine existing genetic variability. The extrapolated ANOVA for different yield contributing parameters showed a high degree of variation among the genotypes used. Correlation co-efficient analysis revealed that yield plant−1 (g) had positive and significant association with ear girth (cm), 1000-kernel weight (g), yield plot−1 (g), grain yield (tha−1) with dry weight. The genotypes differed significantly for most of the phenotypic traits. The phenotypic co-efficient of variation (PCV) was higher than genotypic co-efficient of variation (GCV) in all traits studied indicating that those traits were interacted with the environment. The traits under study expressed wide heritability estimates (26.81% to 99.95%). Among the characters, highest heritability was recorded for 1000-kernel weight (g). High heritability along with high genetic advance was noticed for 1000-kernel weight (g), yield plot−1 (g)and grain yield (tha−1). Considering different desirable traits P-12, Popcorn, V90-1, 988 were observed as superior genotypes. The data would be useful for proper identification and selection of appropriate parents in breeding programs to develop new maize varieties. J. Bangladesh Agril. Univ. 15(2): 193-198, December 2017